Archaeological Investigations in Western Luristan. Preliminary Report of the Second Danish Archaeological Expedition to Iran - Thrane, Henrik (1964)
ersch. 1965; Fortsetzung von 27:d:653; Introduction – Sanctuary – Settlements – Graves – Conclusions. Sites: Tang-i- Hamamlan; Tang-i-Hamamlan-i-kutchek – Kuran Buzan settlement – Cham Qala – Sar Cham – Tepe Chasmeh Mahi – Tepe Guran – Tepe Kazabad – Kahreh – Shir-i-Chigha – Tepe Jarali (Sar-i-Tarhan valley) – Derechte Tabir (Sar-i-Tarhan valley) – Sar-i-Tarhan (village) – Kül Voim – Kushki – Tarhan – Kuh-i-Dasht – Surkh Dum-i-Luri – Surkh Dum-i-Laki – Kheylavar (Kishmahar valley) – Sheikh Hassan (Kishmahar valley) – Barajula (Kishmahar valley) – Bolouran (Boluoran valley) – Tullabi – Imamzadeh Shahzadeh Mohammad – Müreh Kan – Qala Tapoli – Vesgur (Vesgur valley).